“我們不能控裁我們的青春”——嚴歌苓及其“文革”題材小説解讀: We Cannot Manipulate Our Youth: An Examination of Yan Geling and Her Novels on the Great Cultural Revolution - 錢虹 (人文中國學報, 2012)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 近年來，美籍華人女作家嚴歌苓在國内越來越“走紅”。但人們關注得較多的，往往是她那些“虚構”型文本，如《扶桑》、《小姨多鶴》、《第九個寡婦》、《金陵十三叙》等。本文則選取《灰舞鞋》等有關“文革”題材的“穗子的故事”系列小説，從作品與作者生活經歷的重合度、小説的“自傳”色彩、時代的印象寫真、殘酷的青春記憶等方面，做較爲深入的解讀與剖析，并以此凸顯嚴歌苓有關“文革” American-Chinese writer Yan Geling is becoming more and more popular in Mainland China. However, most attention focuses on her fictional works, such as Fusang (Japan), Xiaoyi Duohe (Little Aunty Duohe), and Dijiuge guafu (The Ninth Widow). The present essay focuses on “Stories of Suizi, “a series of works on the Great Cultural Revolution. The discussion involves several aspects; the similarity between the author’s life and that depicted in the story, the autobiographical feature of the work, likeness of the image of the time, and the cruel memory of youth. The in-depth examination and interpretation of these aspects will highlight the value of Yan Geling’s “Impressionist” novels on the Great Cultural Revolution. 題材小説的“印象派”版本的價值與意義。